A prospective observational study of nurses performing minimally invasive tissue sampling of brain, liver, and lung tissues among deceased neonates and stillbirths in Ethiopia - Lulu Mussa Muhe; Christina R. Paganelli; Rahell Hailu Ayele; Tigist Desta; Amha Mekasha; Asrat Demtse; Tesfamichael Awoke; Teferi Elfu; Tewodros Yalew Gebremariam; Dagnachew Tamrat; Amanuel Damie Jiffar; Aklilu Mekasha Zenabu; et al. (Frontiers Media S.A., 2023)
BackgroundWith a neonatal mortality rate of 33 per 1,000 live births in 2019, Ethiopia is striving to attain the Sustainable Development Goal target of 12 deaths per 1,000 live births by 2030. A better understanding of the major causes of neonatal mortality is needed to effectively design and implement interventions to achieve this goal. Minimally Invasive Tissue Sampling (MITS), an alternative to conventional autopsy, requires fewer resources and through task-shifting of sample collection from pathologists to nurses, has the potential to support the expansion of pathology-based post-mortem examination and improve mortality data. This paper evaluates the accuracy and adequacy of MITS performed by nurses at a tertiary and general hospital and in the home of the deceased.MethodsNurses in a tertiary and general hospital in Ethiopia were trained in MITS sample collection on neonatal deaths and stillbirths using standardized protocols. MITS sample collection was performed by both pathologists and nurses in the tertiary hospital and by nurses in the general hospital and home-setting. Agreement in the performance of MITS between pathologists and nurses was calculated for samples collected at the tertiary hospital. Samples collected by nurses in the general hospital and home-setting were evaluated for technical adequacy using preestablished criteria.ResultsOne hundred thirty-nine MITS were done: 125 in hospitals and 14 inside homes. There was a perfect or almost perfect agreement between the pathologists and the nurses in the tertiary hospital using Gwet's agreement interpretation criteria. The adequacy of MITS samples collected by nurses in the general hospital was more than 72% when compared to the preset criteria. The adequacy of the MITS sampling yield ranged from 87% to 91% on liveborn neonatal deaths and 76% for the liver, right and left lungs and 55% for brain tissues in stillbirths.ConclusionsThis study demonstrated that task-shifting MITS sample collection to nurses can be achieved with comparable accuracy and adequacy as pathologists. Our study showed that with standardized training and supportive supervision MITS sample collection can be conducted by nurses in a tertiary, general hospital and, at the home of the deceased. Future studies should validate and expand on this work by evaluating task-shifting of MITS sample collection to nurses within community settings and with larger sample sizes.